SIMPLE ADDITIVE WEIGHTING (SAW) METHOD IN DECISION SUPPORT SYSTEM OF SERVICE CENTER LOCATION USING GIS - Ramandeep, Ramandeep (Brilliant International Journal Of Management And Tourism, 2021)
Decision support system is defined as a system that supports the work of a manager or a group of managers in solving semi-structured problems by providing information or suggestions towards certain decisions. The design of this system used the R & D (Research And Development) method approach according to Borg & Gall (1983:775) and the Simple Additive Weighting (SAW) method as the calculation method, while what was taken into account were the criteria, where the criteria were: the number of consumers, center of crowd, access road, security, development potential. This application is made using the PHP programming language, MySql as the database, and the software used are: Adobe Dreamweaver and Apache. The choice of location for the construction of the right service center location is a problem that is being faced by PT. Eltra Various Techniques Semarang. Leaders feel confused in determining the right location for the construction of a service center because there are many things that must be considered so that the construction is not in vain and can overcome company problems. This decision support system is able to provide convenience for company leaders in determining the right service center location, through appropriate calculation processes and an integrated system with Geographic Information System (GIS) that can point to locations directly online. The results obtained are Tunjungan Elektronik Center with a value of 97.00, ITC Mega Wholesale with a value of 87.00, Galaxy Mall with a value of 86.00, Delta Plaza with a value of 85.00, Hi-tech Mall with a value of 84.00, Citra Wold Surabaya with a score of 83.00 so that the alternative chosen is Tunjungan Elektronik Center with the highest score of 97.00